Framework for Empirical Process to Improve Nonnuclear Gauge Performance in Hot-Mix Asphalt Pavement Construction - Cho, Yong; Wang, Chao; Zhuang, Ziqing (Journal of construction engineering and management, 2013)
AbstractNuclear technology has long been used as a nondestructive method to measure the density of hot-mix asphalt (HMA) during pavement construction. Due to nuclear technology’s high costs and intense regulations associated with safety and security, several researchers have introduced and evaluated nonnuclear technologies for measurement purposes. However, no proven evidence has emerged that nonnuclear gauges can replace nuclear gauges when quality assurance (QA) is considered. Thus, this study developed a framework for an empirical process to improve nonnuclear gauge performance for use in QA and for improving the current quality control (QC) process. Data were collected by coring using a nuclear gauge and using a nonnuclear gauge from 13 HMA paving construction sites over 2 years. A new calibration method was developed for nonnuclear density gauges. The research results reveal that the proposed framework can improve the accuracy of nonnuclear gauges, which can be used for QC and QA of HMA pavement during construction. In addition, nonnuclear gauges showed significant cost savings compared to nuclear gauges from a life-cycle cost analysis.